수모델 활용 저취 시 이중 노즐의 위치 및 중심각에 의한 균일 혼합 시간의 변화 - 나미란; 김선중; Mi Ran Na; Sun-Joong Kim (Resources recycling, 2025)
In the steelmaking process, the stirring by bottom blowing is one of important technologies for homogenizing the temperature and chemical composition of molten steel and removing inclusions, and can improve the refining speed of the process. In general, the stirring energy from bottom blowing is governed by the gas flow rate, the shape parameter of furnace, and the position of nozzle. And the stirring energy affects the perfect mixing time. In this study, we conducted fundamental research to optimize the dual nozzle positions required for multi-nozzle design, based on the nozzle pattern and shape of an industrial furnace process. Using the water model, the influence of the radial position and radian angle of the dual nozzle on the perfect mixing time was investigated by measuring the electrical conductivity. The radial position of dual nozzle varied from 0.15 to 0.70, positioning from the center to a position close to the wall, and the radian angle varied from 30° to 90°. The perfect mixing time obtained from the water model was subjected to regression analysis to derive a relationship between the nozzle radial position, the radian angle, the weight of water, and the gas flow rate. In addition, this study summarizes the optimization conditions and the relationship between stirring energy and perfect mixing time from previously reported water model experiments using dual nozzles. 제강 공정 중 저취 교반은 용강의 온도 및 화학적 조성 균질화, 개재물을 제거하는 중요한 공정 기술이며, 공정의 정련 속도를 개선할 수 있다. 저취 교반에 의한 교반 에너지는 일반적으로 가스 취입량, 로의 형상, 노즐의 설치 위치 등의 영향을 받는다. 그리고 교반 에너지는 속도론적 개념에 있어서 균일 혼합시간을 결정짓는 중요한 요소이다. 본 연구에서는 실제 전로 공정의 노즐 패턴 및 형상에 기반하여 다중 노즐 설계에 있어서 필요한 2중 노즐 위치의 최적화에 대한 기초 연구를 진행하였다. 수모델을 활용하여 2중 노즐의 반경 위치 및 중심각의 영향에 따른 균일 혼합시간의 변화를 전기전도로 측정을 통해 조사하였다. 노즐 반경 위치는 0.15 ~ 0.70로 중심부에서 로벽에 가까운 위치로 변화하였으며, 중심각의 변화는 30° ~ 90°로 변화하였다. 수모델 실험으로 얻어진 균일혼합시간을 회귀분석하여 노즐의 반경 위치 및 중심각, 물의 용량, 가스 유량 등과의 관계식을 도출하였다. 또한, 기존에 보고된 2중 노즐을 사용한 수모델 실험의 최적화 조건, 균일혼합시간과 교반에너지의 관계식을 본 연구에서 정리하였다.